Colorectal cancer biomarker discovery and validation using LC-MS/MS-based proteomics in blood: truth or dare?. (August 2014) - Reumer, Ank; Maes, Evelyne; Mertens, Inge; Cho, William CS; Landuyt, Bart; Valkenborg, Dirk; Schoofs, Liliane; Baggerman, Geert
<x xml:space="preserve">Abstract</x> Globally, colorectal cancer (CRC) is the third most common malignant neoplasm. However, highly sensitive, specific, noninvasive tests that allow CRC diagnosis at an early stage are still needed. As circulatory blood reflects the physiological status of an individual and/or the disease status for several disorders, efforts have been undertaken to identify candidate diagnostic CRC markers in plasma and serum. In this review, the challenges, bottlenecks and promising properties of mass spectrometry (MS)-based proteomics in blood are discussed. More specifically, important aspects in clinical design, sample retrieval, sample preparation, and MS analysis are presented. The recent developments in targeted MS approaches in plasma or serum are highlighted as well.